Exposure to air pollution in early childhood and the association with Attention-Deficit Hyperactivity Disorder - Thygesen, Malene; Holst, Gitte Juel; Hansen, Birgitte; Geels, Camilla; Kalkbrenner, Amy; Schendel, Diana; Brandt, Jørgen; Pedersen, Carsten Bøcker; Dalsgaard, Søren (Environmental research, 2020)
Exposure to air pollution in early life has been linked to cognitive deficits and adverse neurodevelopmental effects. However, studies examining associations between air pollutants and Attention-Deficit/Hyperactivity Disorder (ADHD) have had conflicting findings. Individuals born in Denmark 1992–2007 (n = 809,654) were followed for the development of ADHD from 1997 to 2013. Data on daily concentrations of nitrogen dioxide (NO2) and fine particulate matter (PM2.5) from air-modeling data at a 1 km × 1 km resolution at residences within the first five years of life, was linked with population-based data from the Danish national registers, including data on clinical diagnoses of ADHD. We estimated incidence rate ratios (IRRs) with 95% confidence intervals (CI) for ADHD, according to increases in exposures, adjusting for age, year, sex, and parental education and income. Exposure to NO2 and PM2.5 during early life was associated with a significantly increased risk of ADHD: IRR of 1.38 (Cl: 1.35 to 1.42) per 10 μg/m3 increase in NO2 and an IRR of 1.51 (Cl: 1.41 to 1.62) per 5 μg/m3 increase in PM2.5. In two-pollutant models, the association between NO2 and ADHD did not change (IRR 1.35; 95% CI: 1.31 to 1.39), while the association with PM2.5 was substantially attenuated (IRR 1.07; 95% CI: 0.98 to 1.16), although in stratified models an elevated association with PM2.5 was found in the lowest quintile of NO2 exposure. In this large nationwide prospective cohort study, residential air pollution exposure, specifically NO2, during early childhood was associated with the development of ADHD, even when adjusted for parental level of income and education.